2018
DOI: 10.1002/ima.22269
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced brain image retrieval using carrier frequency offset compensated orthogonal frequency division multiplexing for telemedicine applications

Abstract: Wireless technology plays a vital role in the Electronic health (e‐health) applications such as telemedicine and remote patient monitoring. One of the major challenges of telemedicine applications is ensuring adequate quality of service and realizing precise diagnosis. Telemedicine employs image fusion to enhance the quality of medical image for better diagnosis. However, the transmission of medical image needs high data rate and bandwidth. Due to the robustness to multipath fading, high data rate transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The size of the image considered for the simulation is 128 × 128 shown in Figure 15A. It clearly shows that the presence of CFO degrades the image quality, 26 shown in Figure 15B. The reconstructed image in Figure 15C,D,E shows that the proposed algorithm offers better quality image compared to MUSIC and MLE.…”
Section: Resultsmentioning
confidence: 96%
“…The size of the image considered for the simulation is 128 × 128 shown in Figure 15A. It clearly shows that the presence of CFO degrades the image quality, 26 shown in Figure 15B. The reconstructed image in Figure 15C,D,E shows that the proposed algorithm offers better quality image compared to MUSIC and MLE.…”
Section: Resultsmentioning
confidence: 96%
“…Cruz et al [23] developed a mobile teleradiology system that is suitable for facilitating the CBMIR process. Chitra et al [24] proposed an improved retrieval algorithm for brain images using carrier frequency offset compensated OFDM technique for telemedicine scenarios. Jiang et al [25] tried to solve the "semantic gap" of the CBMIR using the crowdsourcing model in the MTN, which is empirically verified to be both successful and efficient.…”
Section: Pr Jmentioning
confidence: 99%
“…A mobile teleradiology system [ 27 ] is appropriate for streamlining the CBMIR procedure. For telemedicine applications, Chitra et al [ 28 ] suggested an enhanced retrieval approach for brain images utilizing carrier frequency offset adjusted OFDM technique. To solve the ‘ semantic gap ’, Jiang et al [ 29 ] introduced a novel framework of mobile similarity retrieval of medical images based on a crowdsourcing model.…”
Section: Introductionmentioning
confidence: 99%